2(x+-3)+(x+-3)=3

Simple and best practice solution for 2(x+-3)+(x+-3)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+-3)+(x+-3)=3 equation:



2(x+-3)+(x+-3)=3
We move all terms to the left:
2(x+-3)+(x+-3)-(3)=0
We add all the numbers together, and all the variables
2(x-3)+(x-3)-3=0
We multiply parentheses
2x+(x-3)-6-3=0
We get rid of parentheses
2x+x-3-6-3=0
We add all the numbers together, and all the variables
3x-12=0
We move all terms containing x to the left, all other terms to the right
3x=12
x=12/3
x=4

See similar equations:

| 6x+18=-6x-9 | | 2/3(6+x)=24 | | -77-v=v-3 | | x+2=6+(3x) | | 12x3-26x-14=0 | | (4a-4)=(a+6) | | 6=d9 | | (4r+7)=(2r-3) | | 7x+7(x-2)=56 | | 11x-5=12x-11 | | 2x+4x=8x+10 | | 11x–5=11x–5 | | 11t–5=11t–5 | | 2+-x=15 | | 1/5x+5=12 | | 4x+27=3x+49 | | F(x)=14-0.5×30 | | -7=5+u/2 | | .5(r+2.5)=3 | | 9/7=-2/b | | 2q+10=12 | | 2x+3=-3x-12 | | 24=14y-8 | | 5/3x+-4/3x+-1=8 | | 21y=-42 | | 31.25(p+5)=750 | | 6x-(7)=13+2x | | 7c-2c+2c-2c=5 | | 15q-11q-3q=17 | | 8h+18h+-16h+-6h+13h=-17 | | 20q-18q+2q+q-q=16 | | 3x-15=2x(x-5) |

Equations solver categories